2013
DOI: 10.1530/joe-12-0449
|View full text |Cite
|
Sign up to set email alerts
|

Male pubertal development: are endocrine-disrupting compounds shifting the norms?

Abstract: Endocrine-disrupting compounds (EDCs) are synthetic or natural compounds that interfere with endogenous endocrine action. The frequent use of chemicals with endocrine active properties in household products and contamination of soil, water, and food sources by persistent chemical pollutants result in ubiquitous exposures. Wildlife observations and animal toxicological studies reveal adverse effects of EDCs on reproductive health. In humans, a growing number of epidemiological studies report an association with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
60
0
6

Year Published

2015
2015
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 84 publications
(66 citation statements)
references
References 80 publications
0
60
0
6
Order By: Relevance
“…There is great concern about the effects of endocrine disrupting compounds, including chemicals such as bisphenol A (BPA), polychlorinated biphenyl, and phthalates, on pubertal timing in boys. 34 Given that BPA binds to estrogen receptors, there is concern that BPA exposure may lead to earlier onset of puberty in girls, 35 but the effects are unknown for boys.…”
Section: Discussionmentioning
confidence: 99%
“…There is great concern about the effects of endocrine disrupting compounds, including chemicals such as bisphenol A (BPA), polychlorinated biphenyl, and phthalates, on pubertal timing in boys. 34 Given that BPA binds to estrogen receptors, there is concern that BPA exposure may lead to earlier onset of puberty in girls, 35 but the effects are unknown for boys.…”
Section: Discussionmentioning
confidence: 99%
“…One study in Poland reported an over 3-month decrease between 2000 and 2010 in the age of initial appearance of pubic hair in boys (12). Another study in Thailand showed that the age at testicular enlargement Tanner exposures, which may be related to the trend of earlier pubertal onset (26)(27).…”
Section: Discussionmentioning
confidence: 99%
“…Speculations of the origins of such a trend include rapidly changing environmental factors such as chemical exposure [2,4,26] and dietary shifts and a concomitant trend for increased adiposity in children [13].…”
Section: Introductionmentioning
confidence: 99%